Intelligent Decision Technologies 2019 Proceedings of the 11th KES International Conference on Intelligent Decision Technologies (KES-IDT 2019), Volume 2 - Czarnowski, Ireneusz; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book presents a collection of peer-reviewed articles from the 11th KES International Conference on Intelligent Decision Technologies (KES-IDT-19), held Malta on 17-19 June 2019. The conference provided opportunities for the presentation of new research results and discussion about them. It was also an opportunity to generation of new ideas in the field of intelligent decision making. The range of topics explored is wide, and covers methods of classification, prediction, data analysis, decision support, modelling and many more in such areas as finance, cybersecurity, economy, health, management and transportation. The topics cover also problems of data science, signal processing and knowledge engineering.
Quality Improvement Through the Preventive Detection of Potentially Defective Products in the Automotive Industry by Means of Advanced Artificial Intelligence Techniques -- An Efficient Non-Blind Steering Vector Estimation Technique For Robust Adaptive Beamforming With Multi-Stage Error Feedback -- The P2P-Grid-Agent Distributed Platform: A Distributed and Dynamic Platform for Developing and Executing Large Scale Application based on Deep Learning Techniques -- Recognition of Daily Human Activities Using Accelerometer and sEMG Signals -- Classification of Alzheimer's Disease from Structural Magnetic Resonance Imaging using Particle-Bernstein Polynomials Algorithm -- Selecting Informative Samples for Animal Recognition in the Wildlife -- Genetic Algorithm for Selecting Relevant Regions in Digital Watermarking Scheme for 2D/3D Medical Images -- A Transport Coding Gain Estimation in the Conditions of Time Limitation for Maximum Acceptable Message Delay -- Modeling Customers Speed of Movement from POS and RFID-data -- Discovering and Analyzing Binary Codes Based on Monocyclic Quasi-Orthogonal Matrices -- The Study of Generators of Orthogonal Pseudo-Random Sequences -- Portraits of Orthogonal Matrices as a Base for Discrete Textile Ornament Patterns -- Training Sample Generation Software -- Business AI Alignment Modeling Based on Enterprise Architecture -- Eye Tracking as a Method of Neuromarketing for Attention Research - an Empirical Analysis Using the Online Appointment Booking Platform from Mercedes-Benz -- A Concept of an Interactive Web-Based Machine Learning Tool for Individual Machine and Production Monitoring -- Benefits of Agile Project Management in an Environment of Increasing Complexity - A Transaction Cost Analysis -- Potential Benefits of Digital Business Models and Its Processes in the Financial and Insurance Industry -- Risk-Sensitive Decision Making under Risk Constraints with Coherent Risk Measures -- Mutual Evaluation and Solution Method -- Visualization of Criteria Priorities Using a Ternary Diagram -- Changes in Organizations Due to Management Mechanization (Case Studies of Life Insurance Companies in Japan) -- Naturality for Ranking from Pairwise Comparisons -- Upper Level Processes and Projects Model-Building -- SPCM with Harker Method for MDAHP including Hierarchical Criteria -- Building a Telemedicine System for Monitoring the Health Status and Supporting the Social Adaptation of Children with Autism Spectrum Disorders -- Implementation of Digital Technologies in Pharmaceutical Products Lifecycle -- Home Hospital e-Health Centers for barrier-free and cross-border Telemedicine Ralf Seepold, Maksym Gaiduk -- Data Driven Human Movement Assessment -- Attitudes to Telemedicine, and Willingness to Use in Young People -- Posture Tracking Using a Machine Learning Algorithm for a Home AAL Environment.
Keywords: Computational intelligence; Artificial intelligence; Telecommunication; Computational Intelligence; Artificial Intelligence; Communications Engineering, Networks